P501 Safety of peri-operative biologics in patients with IBD undergoing resective bowel surgery: experiences of a single center cohort. (30th January 2023) - Ochsenkuehn, T; Tillack-Schreiber, C; Bader, F; Maximilian, S; Szokodi, D; Tomelden, J; Waggershauser, C; Braun, I; Schnitzler, F
Abstract: Background: Despite good safety data, the risk of peri-operative treatment with biologics in IBD is still discussed controversially. Recently, the prospective PUCCINI trial demonstrated that direct exposure to TNF-blockers within 12 wks. of abdominal surgery was not associated with more infectious complications. However, in daily clinical practice experiences on biological treatment peri-operatively are limited. In our current retrospective trial, we addressed the safety of different biologicals in a peri-operative setting. Methods: Eligible pat. in this single center study were recruited from our IBD center between 2012 and 2022. Direct exposure to biologics was defined as exposure to biologics within 12 wks. before resective bowel surgery performed at our surgical department. To evaluate safety, the post-operative outcome focused on minor complications, defined as infectious complications, wound healing complications and major complications, defined as insufficiency of the anastomosis and abscess formation at surgery site post-operatively. Results: A total of 447 IBD pat. (334 CD, 113 UC, 51.9% female) were included and followed for a median of 45 mo. [range 0-113]. Median age was 44 yrs. [19-89], median age at diagnosis was 24 yrs. [5-84] and median age at surgery was 41 yrs. [16/85]. Median disease duration until surgery was 11 yrs. [0-47]. 74.3% of pat. had moderate to severe disease activity at date of surgery. A total of 73.9% of pat. (326/447) had medical treatment at date of surgery, 61.5% of pat. (275/447) were treated with biologics within 3 mo. before surgery and 42.3% (189/447) had biologic treatment within 4 wks. before surgery. Overall, 36.9% of pat. (164/447) received infliximab, 13.0 % (58/447) adalimumab, 1.1% (6/447) golimumab, 5.8% (26/447) vedolizumab, and 6.5% (29/447) ustekinumab, peri-operatively. Most surgeries were planned electively (97.1%, 434/447) and performed laparoscopically (67.8%, 303/447). Minor and major post-operative complications occurred in 20.8% (93/447) of patients. Serious complications were observed in 9 pat., six had acute bleeding, one developed peritonitis and two died post-operatively (one with and one without biologics). Using logistic regression models, no significant differences regarding complications and safety were observed between pat. with versus without biologic treatment. Interestingly, CD pat. with direct exposure to biologics within 4 wks. were more likely to undergo minimal-invasive surgery (68.6%, 107/156) than pat. with biologics within 3 mo. before surgery (48.28%, 28/58, p=0.02). Conclusion: This retrospective single center study of 447 IBD patients could demonstrate that biologic treatment before surgery, even within 4 wks, is not associated with a higher risk of complications.